Permasalahan Pelaksanaan Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kota Padang - Afriyanni . (Jurnal Pembangunan Nagari, 2018)
PATEN is a new public management centered in the sub-district to improve the quality and bring the service closer to the community. Since Regulatory of minister Affair number 4 in 2010 was declared. The Implementation of PATEN in Indonesia nowdays reach 15 percent. This research aims to identify the problem of impelementation PATEN in Pilot district projects in Padang in order to provide recommendation for PATEN implementation. This study used descriptive qualitative research through observation, documentation and interview in collecting data. The result showed that there are a number of obstacles in the implementation of PATEN namely the delegation of authority, procedures, human resources, limited facilities and infrastructure. For That, it is amust for the Local Government to handle those problems